Importance of the ITF Junior Girls' Circuit in the development of women professional tennis players - Reid, M.; Crespo, M.; Santilli, L. (Journal of Sports Sciences, 2009)
In this study, we examined the extent to which ranking in professional women's tennis can be predicted by that in the top 20 International Tennis Federation's Junior Circuit. The names, nationalities, and birth dates of all players who achieved a top-20 girls' year-end ranking from 1995 to 2002 were recorded, with their progress through the professional ranks tracked to March 2008. Ninety-nine percent of top-20 ranked girls achieved a professional women's ranking. Stepwise regression analysis revealed peak junior ranking and the age at which that rank was achieved to be predictors of future professional ranking (r2 = 0.133, P < 0.05). The following regression equation showed the achievement of a top-20 junior rank as a reasonable benchmark in the development of professional women players: log-transformed predicted professional rank = -0.552 + (0.032 junior rank + 0.116 age at junior rank). The predominant court surface on which junior players honed their skills was also implicated in professional ranking success, with clay-court play linked to the development of higher-ranked players (P = 0.01).